Sustainable Marketing Strategies for Incoming Students to Chinese Universities - Chen, Zongsheng; Constantin, Cristinel Petrișor (MDPI AG, 2024)
This paper investigates the motivations and satisfaction levels of international students studying in China, using a marketing approach. Through a literature review, it examines education service quality, marketing tools, and the importance of international students. The main goal is to identify the main incentives for students coming to China and to assess the gaps between their expectations and satisfaction with various aspects of the marketing mix during their studies. To achieve this goal, a quantitative survey was conducted, which reveals that the most valued incentives are related to the campus environment, professional teachers, student life, and cultural diversity. In terms of student satisfaction, the results highlight that the least satisfactory factors include aspects related to the promotion of international studies and the partnerships between universities. These areas require more attention from Chinese university management for future improvement. The paper concludes with theoretical implications and managerial recommendations for universities, national policymakers, and Chinese authorities in the context of China's national education development strategy, entitled "Opinions on Accelerating and Expanding the Opening Up of Education to the World in the New Era".